2018
DOI: 10.1111/jfpe.12953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of açaí pulp, cheese whey, and hydrolysate collagen on the characteristics of dairy beverages containing probiotic bacteria

Abstract: The aim of this study was to evaluate the effect of hydrolysate collagen (HC), cheese whey (CW), and açaí pulp (AP) content on the characteristics of probiotic dairy beverages. Higher levels of CW and AP decreased beverage ash and protein content, and increased lipid and carbohydrate content and energy values. HC and AP positively affected the viscosity of the formulations, which exhibited pseudoplastic behavior. In terms of quality parameters, higher levels of CW and AP increased both the syneresis (2.56–5.74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The above statements were confirmed in our study, because the use of 3% collagen protein hydrolysate in milk did not negatively affect the organoleptic characteristics of milk fermented with both Bifidobacterium Bb-12 and by L. rhamnosus. da Mata Rigoto et al [35] obtained similar results in probiotic dairy beverages produced with hydrolysate collagen. Authors showed that hydrolysate collagen addition did not affect the apperance, aroma, flavour or texture of this beverages.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The above statements were confirmed in our study, because the use of 3% collagen protein hydrolysate in milk did not negatively affect the organoleptic characteristics of milk fermented with both Bifidobacterium Bb-12 and by L. rhamnosus. da Mata Rigoto et al [35] obtained similar results in probiotic dairy beverages produced with hydrolysate collagen. Authors showed that hydrolysate collagen addition did not affect the apperance, aroma, flavour or texture of this beverages.…”
Section: Discussionmentioning
confidence: 67%
“…However, such a relationship was not confirmed in the case of milk fermented by L. rhamnosus. The results obtained by da Mata Rigoto et al [35] showed that hydrolysate collagen addition in probiotic beverages had a minor or no effect on Lactobacillus acidophilus culture viability. Moreover, collagen addition in dairy beverages offered functional appeal due to the continued viability of probiotic bacterias during the storage time.…”
Section: Discussionmentioning
confidence: 98%
“…The development of a fermented dairy drink using ricotta cheese whey with HC added as a functional ingredient presented low syneresis and sedimentation, with good physical–chemical and microbiological properties [132]. Dairy beverages using HC, açaí pulp, and cheese showed higher sensorial acceptability, affecting positively the viscosity and presenting adequate physicochemical and microbiological parameters after 28 days of storage [133].…”
Section: Hydrolyzed Collagen: Sources and Applicationsmentioning
confidence: 99%
“…lactis BB-12 and Propionibacterium jensenii 702 were made by Ranadheera et al [21], with no negative effects on the sensory properties. Collagen hydrolysate, cheese whey, and acai pulp ( Euterpe oleracea ) have been successfully incorporated in fermented goat milk beverages to extend the viability of probiotics [22]. SHIME is a unique scientifically validated dynamic model of the complete gastrointestinal tract for study of physicochemical, enzymatic, and microbial parameters in the gastrointestinal tract in a controlled in vitro setting.…”
Section: Current Status Of Goat Dairy Productsmentioning
confidence: 99%